1970
DOI: 10.3329/bjpbg.v23i2.9324
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Local Rainfed Rice (<i>Oryza Sativa</i> L.)

Abstract: Genetic diversity of 58 traditional local rice genotypes was studied under rainfed condition through Mahalanobis D 2 statistic for grain yield and yield contributing characters. The genotypes were grouped into nine clusters. The inter-cluster distances were higher than intra-cluster distances indicating wider genetic diversity among the genotypes of different clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. The cluster III contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
4
3
0
Order By: Relevance
“…The intra-cluster distances were low for all the six clusters with the range of 0.755 in cluster V to 1.347 in cluster VI which indicated homogeneous nature of the genotypes within the clusters. The results were supported by the findings of Siddique et al (2010 and2011) in rice. The inter-cluster distances ranged from 4.732 to 17.815 and PCoA scores also indicated a high degree of genetic diversity among the genotypes.…”
Section: Resultssupporting
confidence: 81%
“…The intra-cluster distances were low for all the six clusters with the range of 0.755 in cluster V to 1.347 in cluster VI which indicated homogeneous nature of the genotypes within the clusters. The results were supported by the findings of Siddique et al (2010 and2011) in rice. The inter-cluster distances ranged from 4.732 to 17.815 and PCoA scores also indicated a high degree of genetic diversity among the genotypes.…”
Section: Resultssupporting
confidence: 81%
“…The intra-cluster distances were low for all the six clusters with the range of 0.525 in cluster IV to 0.637 in cluster II which indicated apparently homogeneous nature of the genotypes within the clusters. The results were supported by the findings of Siddique et al (2010 and2011) in rice. The intercluster distances ranged from 3.352 to 10.168 and PCoA scores also indicated a high degree of genetic diversity among the genotypes.…”
Section: Quantitative Traits Characterizationsupporting
confidence: 81%
“…As a result, the genotypes under cluster III with clusters IV, V and VI, might be selected as parents for future breeding program depending upon the objectives. Hosan et al (2010), Siddique et al (2010Siddique et al ( , 2013 and Sohrabi et al (2012) earlier reported similar trend of conclusions on rice using Mahalanobis' D 2 statistics. Therefore, the genotypes under cluster III, cluster IV, cluster V, cluster VI might be selected for future breeding program.…”
Section: Resultssupporting
confidence: 56%